A Retrospective Chart Review to Determine Lateral Ankle Instability Treatment based off of the Degree of Varus Tilt. Issue 4 (22nd October 2020) - Brandle, Greggory; Rizzo, Kaitlyn; Cheney, Nicholas A.; Clark, Brian C.
Category: Ankle Introduction/Purpose: One of the most common injuries in the United States is the ankle sprain, accounting for 10-15% of sport injuries. Without proper treatment, about one-third of patients reinjure the same ankle and can progress to chronic lateral ankle instability. An ankle can be clinically evaluated by performing an inversion stress test and measuring the degree of varus tilt. The purpose of this retrospective chart review was to examine if a correlation exists between the degree of varus tilt on a stress x-ray and whether the patients were treated conservatively or surgically. Additionally, this chart review aims to confirm the validity of the guidelines of an abnormal talar tilt value, which is said to be a value greater than 10 degrees. Methods: A total of 584 patients between January 1st, 2016 and June 27th, 2019 were clinically diagnosed with lateral ankle instability and had an inversion stress x-ray. All 584 patients were seen and diagnosed by the same foot and ankle orthopedic surgeon in Columbus, Ohio. Of the 584 patients, 40 had bilateral lateral ankle instability and bilateral stress xrays, given a total of 624 ankles originally included in this chart review. Once the patient's charts were reviewed, 32 ankles were excluded because their ankle surgery did not involve correction of the lateral ankle instability. A total of 592 ankles (293 left and 299 right) were included in this review. The degree of varus tilt on all 592 ankles were determined by measuring the angle between the tibial plafond and the top of the talus. The angles were compared to the patients with surgical and conservative treatment. Results: The chart review showed that as the degree of varus tilt increases, the more likely the patient is to fail conservative treatment and need surgical correction. The types of conservative treatment that the patients failed were a combination of a brace, boot, physical therapy, orthotics, shoe changes, injection, and casting. The patients who had a varus tilt below 2.5 degrees were treated conservatively 60% of the time, where patients that had a varus tilt over 20.1 degrees were treated surgically 75% of the time. The review also showed a significant number of patients who were treated surgically with a varus tilt value less than 10 degrees (209 of 472 ankles), warranting further evaluation into what is considered an abnormal talar tilt. Conclusion: It is clear that patients with a higher degree of varus tilt have more ankle instability and are more likely to fail conservative treatment and require surgical correction. Additionally, this chart review showed that many patients needed surgical correction even with a low varus tilt value on stress x-ray. Further evaluation needs to be completed to determine what value is considered an abnormal varus tilt. One possible explanation of our findings is that the inversion stress test does not evaluate the subtalar joint, which can contribute to chronic lateral ankle instability.